A note on recent surveys for right whales in the southeastern Bering Sea - LeDuc, R.G.; Perryman, W.L.; Gilpatrick, J.W.; Hyde, Jr., J.; Stinchcomb, C.; Carretta, J.V.; Brownell, Jr., R.L. (J. Cetacean Res. Manage., 2020)
Research vessel and aerial platforms were used between 1997 and 2000 to collect genetic and photographic data from a small population of right whales that summers in the southeastern Bering Sea. Totals of 11 and six unique individuals were identified using photographic and genetic methods, respectively. Single matches between years occurred using both methods, and all genetic samples turned out to be from male whales. Long-term research is needed to estimate the size of this population and to determine what threats the whales may be facing.